Microservices for Java developers : a hands-on introduction to frameworks and containers - Benevides, Rafael; Posta, Christian (O'Reilly Media, 2019)
Is microservice architecture right for your organization? Microservices have many benefits, but they also come with their own set of drawbacks. With this updated edition, Java developers and architects will learn how to navigate popular application frameworks such Spring Boot and MicroProfile to deploy and manage microservices at scale with Linux containers. This hands-on, example-driven guide provides step-by-step instructions to help you get started. Adopting microservices requires much more than changes to your technology. Author Rafael Benevides, director of developer experience at Red Hat, also examines the organizational agility necessary to deliver these services. This concise ebook shows you how rapid feedback cycles, autonomous teams, and shared purpose are key to making microservices work. Learn why microservices require you to think differently about building, deploying, and operating cloud-native applications Design microservices using the popular Spring Boot and Eclipse MicroProfile frameworks Build an API gateway with Apache Camel to help clients access microservices Use Docker and Kubernetes to deploy microservices, regardless of language Run microservices at scale using cluster management, failover, and load-balancing techniques Use OpenTracing to monitor requests, response time, and the path of particular invocations.